The Impact of Video - Making Activities on Studentâs Grammar Mastery - Mufidah, Nida (Jurnal Tarbiyah : Jurnal Ilmiah Kependidikan, 2017)
The teaching of grammar is frequently uninteresting so most of students are reluctant to learn this subject. Inviting them to learn the grammar by incorporating the use of technology may become a new way to attract their attention. In the present research, the writer conducted a research to compare the impact of grammar instructions on two classes, which used two different techniques to teach grammar: conventional method and video-making activities (VMA). There were 51 students of English Department at State Institute for Islamic Studies who participated in the research. The data were collected by using a test to measure their grammar mastery and a questionnaire to understand their respond toward the method. The resultshowed that the students who were taught by using the VMA had no better grammar mastery compared to those who were taught using the conventional method. However, the result of questionnaire yielded that most of the students agreed that the VMA was fun and interesting. This activity, according to them, also promoted creativity and technology literacy.